NALAR KEBERAGAMAAN MASYARAKAT BANJAR: DARI MISTIS-REALIS HINGGA TRADISIONALIS-KRITIS - Nadhiroh, Wardatun (Pascasarjana UIN ANTASARI Banjarmasin, 2019)
The Banjar community, which consists of the Banjar ethnic group, is referred to as a tribe that overlaps between ethnic and religious identities. When mentioned with the word